Atención al cliente en la Cooperativa de Transporte IMCA del cantón Montalvo-provincia de Los Ríos. - Velásquez Onofre, Patricia Karina (2023)
The present case study named Customer Service in the Imca Transport Cooperative of the Montalvo canton-Los Ríos province - 2022, was carried out with the purpose of knowing the attention that users currently receive, if it is adequate and if it is impacting positively or negatively to the company. Each of the existing problems were described, based on the quality of the Cooperative's transport service, offered in various cantons and parishes, evaluating the customer service process, the strategies and techniques required to satisfy users, the method that was applied in this investigation is the cause - root which allowed to discover the origin of the problems to be able to implement a solution to them. The techniques and instruments used to carry out the case study were the interview and the survey, where the interview was carried out with the owner of the Cooperative and the survey was carried out with the clients, knowing their suggestions and points of view regarding the service offered. Obtaining highly valid results to collect accurate information and execute various strategies in order to improve the care provided, increase sales, differentiate from the competition and thus achieve all its objectives and goals of the organization.